Meningkatkan Pemahaman Strategi Pemasaran dan Penerapan Digital Marketing pada UMKM Dusun Mulyorejo: Studi Kasus pada Kelompok Usaha “Kinanti Snack” di Desa Limbung, Kecamatan Sungai Raya, Kubu Raya - Safitri, Dayang Annisa; Daud, Ilzar; Sudjono, Denzel; Fajryn, Marleny; Dinata, Febtian Aaron (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Small and Medium Enterprises (SMEs) play a strategic role in Indonesia's economy, but one of the main challenges they face is the limited scale of marketing, particularly in utilizing digital technology. This Community Service Program (PKM) aims to improve the understanding and implementation of digital marketing strategies for SMEs, specifically for the business "Kinanti Snack" in Dusun Mulyorejo, which until now has relied on conventional marketing. Through this mentoring activity, participants were involved in training on how to use social media platforms, such as Instagram, to promote products more effectively. They also learned how to use applications like Canva to create engaging promotional content. Additionally, participants took part directly in the production process of various traditional snack products. This activity provided dual benefits: helping SMEs expand their market reach and increase sales through digital marketing strategies, while also offering participants new experiences in the micro-business world. With proper implementation of digital marketing, SMEs can become more competitive and adaptable to the evolving times, contributing to local economic stability and growth.